Investigation of PH effect in a mixture of basalt and iron on co2 sequestration in synthetic brines - Ajayi, Toluwaleke (International Journal of Advanced Geosciences, 2019)
CO2 sequestration in deep saline aquifers is a critical component of long-term storage options. It is suggested that the precipitation of mineral carbonates is mostly dependent on brine pH and is favoured above a basic pH of 9.0. However, brine pH will drop to acidic values once CO2 is injected into the brine. Therefore, there is a need to raise brine pH and maintain it stable. Synthetic brines were used here instead of natural brines because of the difficulty in obtaining and storing natural brines. Therefore, experiments were conducted to prepare a series of synthetic brines and to compare their suitability to natural brines for carbon sequestration. A typical formation rock (basalt) and a buffer solution (0.3M Tris buffer solution) were selected to buffer brine pH. The results show that synthetic brines prepared can be used as analogues to natural brines for carbon sequestration studies in terms of chemical composition and pH response. This study investigates the effect of iron ( ) in the pH of six synthetic brines prepared as analogue to oil-field brine by conducting a pH stability studies for CO2-brine experiment and CO2-basalt-brine experiment. In a subsequent step, studies were conducted to correlate how brine samples respond in the presence of basalt and the buffer solution. X-Ray powder Diffraction (XRD) analyses were also carried out to characterise the mineralogy of the synthetic brines. The result of the XRD confirmed that calcite was the major component that was dominated in the -brine–experiment while slight occurrence of calcite, iron oxyhydroxides and dolomite precipitated in the -rock-brine experiment. It was observed that ferric iron  and its reaction with host rock (basalt) did not contribute to pH instability therefore making it suitable for precipitation of carbonate mineral while ferrous iron in the absence of host rock did not contribute to pH instability therefore making it also suitable for precipitation of carbonate mineral.